Diagnostic approach to patients at risk of otogenic skull base osteomyelitis. (1st April 2022) - Lim, Jason Wei Jun; Hill, Fiona C. E.; Kerr, Stephen; Briggs, Robert; McLean, Tim
Abstract: Background: Otogenic skull base osteomyelitis (OSBO) is rare and potentially fatal sequelae of otitis externa. Accurate and timely diagnosis is important due to rising incidence, morbidity and costs associated with treatment. Consensus on the diagnostic approach for OSBO has yet to be reached, in particular the utility of imaging modalities. Aims/objectives: This study reviews a single institution's high-volume experience of OSBO, with the aim of analysing clinicopathologic features and imaging studies to develop a diagnostic algorithm. Material and methods: A retrospective review of patients admitted with OSBO from 2009 to 2019, was performed. After applying inclusion and exclusion criteria, 103 patients with 106 unique episodes of suspected OSBO were selected. De-identified information including patient demographics, clinicopathologic features and imaging outcomes was recorded and analysed. Results: HbA1c ≥ 7% significantly predicted for OSBO in univariate (OR 7.83, 95% CI 1.85–33.16, p = 0.01) and multivariate analyses (OR 5.21, 95% CI 1.05–25.81, p = 0.04). The CT/technetium-99m/gallium-67 combination produced better diagnostic accuracy for OSBO (AUROC 0.96, 95% CI 0.92–1), when compared to a CT/MRI combination (AUROC 0.86, 95% CI 0.79–0.93). Conclusions and significance: Once there is a clinical suspicion for OSBO, diagnosis is established by synthesising results from clinical assessment, pathologic investigations and imaging modalities. The imaging utilised to diagnose OSBO should vary according to the clinical situation and limitations of each modality.